Penggunaan Media Permainan Kotak Sortasi Untuk Meningkatkan Kemampuan Kognitif Mengenal Bentuk Geometri Pada Anak di TK Gmim 15 Tandurusa Kota Bitung - Tutuhatunewa, Fidelvia Oshin; Tiwow, Mieke Farny; Lengkong, Eduard J. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is motivated by the lack of understanding of children about recognising geometric shapes, the purpose of this study is to get an overview of the use of sorting box game media to improve cognitive abilities to recognise shapes in children. The type of research used in the study is classroom action research refers to the Kemis and McTaggart model which has four stages: 1. planning, 2. implementation, 3. observation, 4. reflection. The research subjects were children in GMIM 15 Tandurusa Kindergarten, Bitung City, totalling 10 children. Data collection techniques used are observation and documentation. Research results in cycle I obtained 60% which is where there are still many children who have not reached learning completeness, and continued in cycle II obtained results 100. From the results obtained, it means that the objectives of this study have been successful. The conclusion is that the sorting box game media can improve cognitive abilities to recognise geometric shapes in children